On equiconvergence of Fourier Series and Fourier Integral - Rakhimov, Abdumalik A.; Hassan, Torla; Rasedee, AhmaFadly Nurullah (IOP Publishing, 2017)
In this paper we prove a precise equiconvergence relation between index of the Bochner-Riesz means of the expansions and power of the singularity of the distributions with compact support.